Ayurvedic Approach to Menopause : A Review - Meher, Krishna; Pariksha, Armaan; Priyadarshini, Namrata; Meher, Sudeshna (International Research Journal of Ayurveda & Yoga, 2022)
Menopause marks the permanent cessation of menstruation resulting from irreversible changes in the hormonal and reproductive functions of the ovaries and is associated with large number of symptoms ranging from physical, psychological and genitourinary. In the present scenario menopausal health demands priority due to increase in life expectancy and growing population of menopausal women. Rajonivrittti (menopause) as a diseased condition is not described separately in the classics; Rajonivritti-kala (menopause) is mentioned by almost all Acharyas. Due to changing lifestyle, food habits and socio-economic standards the age is decreasing. By taking into consideration all the references available in Ayurveda classics, efforts have been made to review critically the said subject in the light of Menopausal Syndrome mentioned in modern Medicine as the fundamentals of Ayurveda in this paper.